Santú synchronizing rhythm, speech, and poetry in the gong and bamboo instruments of Panay Bukidnons - Muyco, Maria Christine M. (Musika Jornal, 2013)
This paper explores the concept of santú, or synchronization, in forming gong and bamboo music from rhythmic, speech and poetic sources among the Panay Bukidnon, the highland people of Panay in the Philippines. Building poetry from speech patterns, which involves rhythmic play, feeds into the basic understanding of the connection between speech/language, chanting, and instrument playing. Furthermore, the linkage between language and instrumental sounds and playing depends on understanding the nuances of limog - sounds and tone colors. The linkage to tone nuances helps in determining points where music and dance can synchronize and eventually realize sibod, an ideology rich in meanings that points towards balance and transcendental connections to other realms. Santú is one of the key concepts in sibod and its meaning relates to connectedness as well as to performing in time together. Given its essentially musical and rhythmic meanings, this concept forms a keystone upon which gong and bamboo instrumental performance balances.